2007
DOI: 10.1007/s10620-007-0097-6
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Patterns and Histopathological Features after Eradication Therapy in Helicobacter pylori-Associated Nodular Gastritis

Abstract: The endoscopic finding of nodular gastritis (NG) is highly associated with presence of Helicobacter pylori infection. How the endoscopic patterns and histopathology of NG change after eradication of H. pylori is unclear. Twenty-one adults (3 men and 18 women) with H. pylori-associated NG found on endoscopy were enrolled for this study. The histological findings included gastritis activity, bacterial colonization, and lymphoid follicles. Repeat endoscopy for the endoscopic as well as histopathological features … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 15 publications
2
17
0
1
Order By: Relevance
“…Koh et al [32] found that the increase in gastritis score was dependent on the increase in H. pylori density and was significantly associated with the occurrence of NG. Also, Chen et al [27] in 2008 reported that after treatment of H. pylori , there was a significant improvement in scores for gastritis activity, bacterial colonization and follicular gastritis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Koh et al [32] found that the increase in gastritis score was dependent on the increase in H. pylori density and was significantly associated with the occurrence of NG. Also, Chen et al [27] in 2008 reported that after treatment of H. pylori , there was a significant improvement in scores for gastritis activity, bacterial colonization and follicular gastritis.…”
Section: Discussionmentioning
confidence: 99%
“…H. pylori is predominantly acquired in childhood, and NG has frequently been found in children undergoing endoscopy [6] ; however, NG is present in a minority of adult patients with H. pylori infection; it is unclear how and why that particular pattern develops in only a small proportion of adult patients. Variations in bacterial strains, host factors, or a complex interplay between host and bacterial factors have all been postulated as explanations [27] . H. pylori strains are genetically diverse and could be incapable of inducing constant immune response [28,29] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nodular gastritis, however, is characterized endoscopically by micronodules with a smooth surface and is associated with pediatric patients with H. pylori infection (4,34). It would be clinically desirable to diagnose H. pylori-associated gastritis simply by endoscopic examination without gastric biopsy.…”
Section: Discussionmentioning
confidence: 99%
“…A number of reports have shown microscopic improvement of gastric mucosa after H. pylori eradication; for example, chronic active gastritis, atrophic gastritis, nodular gastritis, and intestinal metaplasia (IM) were diminished by eradication (3,4). In addition, eradication of H. pylori led to a lower prevalence rate of secondary gastric carcinoma in patients with multiple gastric carcinomas at different time points (5,6) and reduction of gastric mucosa-associated lymphoid tissue (MALT) lymphoma (7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%